THE EFFECT OF DIORAMA LEARNING MEDIA ON STUDENTS’ LEARNING ACTIVENESS IN GRADE V AT BAKTI I PRIVATE ELEMENTARY SCHOOL MEDAN - Aprilia Nola Lingga; Chairunnisa Amelia (Journal of Innovation in Research, Education and Culture (JIREC), 2026)
This study was conducted due to the problem of low student learning activeness, where teachers used limited variations of teaching methods and learning media, resulting in only a few students paying attention during lessons. This study aims to determine the effect of using diorama learning media on students’ learning activeness in the IPAS subject for Grade V at Bakti I Private Elementary School Medan.This research is an experimental study. The population consisted of 28 students, including 19 male students and 9 female students. The sampling technique used was total sampling, in which all members of the population were included as the research sample. The instrument used in this study was an observation sheet. The independent variable in this study was diorama learning media, while the dependent variable was students’ learning activeness. Hypothesis testing was conducted using the independent sample t-test, which resulted in a significance value of 0.000 < 0.05. This indicates that Ha is accepted, meaning there is a significant effect of diorama learning media on students’ learning activeness, while H0 is rejected. Thus, it can be concluded that there is a significant effect of diorama learning media on the learning activeness of Grade V students at Bakti I Private Elementary School Medan.